Effect of microwave pretreatment on gaharu essential oil using hydrodistillation method: article / Filzah Anati Kasim and Nurhaslina Che Radzi - Kasim, Filzah Anati; Che Radzi, Nurhaslina (2018)
Gaharu (A.malaccensis) is a valuable resinous heartwood trees that belong to Thymelaeceae family. The objectives of this research were to study the effect of microwave pretreatment on gaharu essential oil using hydrodistillation method, the effect of microwave processing time on gaharu’s oil yield and to study the effect of hydrodistillation time on gaharu’s oil yield. Gaharu sample were pre-treated with microwave irradiation at the power of 800 kW at three different times, which are 1, 2 and 3 minutes. After the pretreatment, gaharu sample were extracted using hydrodistillation method for 30 and 47 hours. The oil produced were weight to determine the percentage of oil yield. Effects of microwave pretreatment were determined using gas chromatography-mass spectrum analysis to study the chemical composition of oil. Hydrodisillation process with microwave pretreatment produce higher yield (0.0379%) of gaharu essential oil compare to non-pretreatment extraction (0.0286%). In addition, higher microwave time (3-min) during the pretreatment also will produce greater amount of oil (0.0877%). As it will break the structure of gaharu for better extraction. Hydrodistillation processing time also gives effect on the amount of produced oil as longer the extraction time, higher the oil yield. Major component of oil contains sesquiterpene such as gurjunene, α-parasinsene, spathulenol and guaiene that were known to offer the sweet wood fragrant in the oil.